Multi-Hit White Matter Injury-Induced Cerebral Palsy Model Established by Perinatal Lipopolysaccharide Injection - Liu, Le; Fang, Liwei; Duan, Boyang; Wang, Yue; Cui, Zhenzhen; Yang, Li; Wu, De (Frontiers in Pediatrics, 2022)
Cerebral palsy(CP) is a group of permanent, but not unchanging, disorders of movement and/or posture and of motor function. Since the major brain injury associated with CP is white matter injury (WMI) especially in preterm infants, we established a “multi-hit” rat model to mimic human WMI in symptomatology and histological level. In our WMI model, pups suffer from limb paresis, incoordination, and direction difficulties, that fit the performance of CP. Histologically they present with less neural cells, inordinate fibers, and more inflammatory cell infiltration, comparing to the control group. From the electron microscopy results, we spotted neuronal apoptosis, glial activation, and myelination delay. Besides, the abundant appearance of IBA1 labelled microglia also implied that microglia play a role during neuronal cell injury. After activation, microglia shift between the pro-inflammatory M1 type and the anti-inflammatory M2 type. The results showed that LPS/infection stimulated IBA1+ (marked activated microglia) expression, downregulated CD11c+ (marked M1 phenotype), and upregulated Arg 1+ (marked M2 phenotype) protein expression. It indicated a M1 to M2 transition after multiple infection. In summary, we established a “multi-hit” WMI-induced CP rat model and demonstrated that the microglial activation correlates tightly with CP formation, which may become a potential target for future studies.